2019
DOI: 10.1002/ece3.5112
|View full text |Cite
|
Sign up to set email alerts
|

Landscape effects on the contemporary genetic structure of Ruffed Grouse (Bonasa umbellus) populations

Abstract: The amount of dispersal that occurs among populations can be limited by landscape heterogeneity, which is often due to both natural processes and anthropogenic activity leading to habitat loss or fragmentation. Understanding how populations are structured and mapping existing dispersal corridors among populations is imperative to both determining contemporary forces mediating population connectivity, and informing proper management of species with fragmented populations. Furthermore, the contemporary processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 92 publications
1
19
1
Order By: Relevance
“…Although not completely congruent with currently designated subspecies of ruffed grouse, observed patterns of genetic variation confirm that ruffed grouse show evidence of population subdivision, and some of this variation coincides with portions of the range of recognized subspecies. For instance, a recent study [10] based on microsatellite and mtDNA markers revealed high levels of population differentiation of populations from Alaska and Washington, with evidence of subdivision for populations from western Canada. Our data indicate that populations containing individuals from Washington, Idaho, and Montana (Group 1) represent one of the most distinct and divergent groups of ruffed grouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not completely congruent with currently designated subspecies of ruffed grouse, observed patterns of genetic variation confirm that ruffed grouse show evidence of population subdivision, and some of this variation coincides with portions of the range of recognized subspecies. For instance, a recent study [10] based on microsatellite and mtDNA markers revealed high levels of population differentiation of populations from Alaska and Washington, with evidence of subdivision for populations from western Canada. Our data indicate that populations containing individuals from Washington, Idaho, and Montana (Group 1) represent one of the most distinct and divergent groups of ruffed grouse.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies clearly document morphological and ecological differences across the ruffed grouse’s range, morphology-based taxonomy is not always congruent with geographic patterns of genetic variation [8], thus making it difficult to identify units of conservation [9]. To the best of our knowledge, the only genetic study of ruffed grouse assesses the landscape genetics of populations from the extreme western range of the species [10].…”
Section: Introductionmentioning
confidence: 99%
“…This site is along the eastern slope of the Rocky Mountains, but the lower elevations contains a comparable forest type to Buck Lake with trembling aspen and white birch ( Betula papyrifera ) stands mixed with assorted conifer species, shrubs, and a few small muskeg patches. We used this second site in April‐May 2016 to sample individuals for a population genetics study (Jensen, O'Neil, Iwaniuk, & Burg, ).…”
Section: Methodsmentioning
confidence: 99%
“…Once caught, each male bird was placed into a dark‐colored pillowcase, weighed with a spring scale (±5 g) and linear measurements taken of the tarsus with plastic calipers (±0.5 mm) and the wing chord with a wing rule (±1 mm). Finally, blood samples were taken using brachial venipuncture for a population genetics study (Jensen et al, ), after which the grouse was released. All procedures adhered to the Canada Council for Animal Care regulations were approved by the University of Lethbridge Animal Welfare Committee and collected under research permits issued by Alberta Environment and Parks.…”
Section: Methodsmentioning
confidence: 99%
“…These SDMs can be a robust source of information in the absence of empirical ecological data 5 7 . In addition to contemporary distributions 8 , 9 , models can be projected onto paleo- and future landscapes to test hypotheses related to temporal range shifts based on changing conditions (e.g. glaciation cycles, future climate predictions 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%